On‐line voltage stability index based on the voltage equation of transmission lines. Issue 14 (1st November 2016) - Ancheng, Xue; Ruihuang, Liu; Mingkai, Li; Chow, Joe H.; Tianshu, Bi; Ting, Yu; Tianjiao, Pu
Abstract : This study proposes a new voltage stability index based on the voltage equation of transmission lines. The proposed index is obtained by using the characteristic that the sensitivity of voltage to power at the voltage collapse point tends to be infinite. Furthermore, the proposed index is also validated in the case of inverse power flow, and the condition of monotonicity is discussed. Simulation results in a single branch system, a 10‐bus system and a regional power system verify the effectiveness of the proposed on‐line voltage index. The simulation results also show that the proposed index is better than the on‐line branch voltage stability index and is more promising for use in industry. The proposed index can be readily calculated from the measurements at the two terminals of the branch, which can be obtained with PMUs. Hence it is suitable for online applications. Finally, issues related to the practical application of the proposed index are discussed.